COMPARATIVE FINANCIAL RATIO ANALYSIS OF COMPANIES IN THE STOCK EXCHANGE OF THAILAND, A CASE STUDY: AUTOMOTIVE PARTS MANUFACTURING COMPANIES. - Teekasap, Sombat; Taeng-on, Suwanna; Keowsiri, Nantawan; Thaweedet, Thikamporn (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
This research deployed a secondary documentary method with the aim to compare; Liquidity, Efficiency, Leverage and Profitability; between companies in Automotive parts manufacturing industry group for investment decision information calculation. Financial statements report during the period of 2013 - 2018 was collected from The Stock Exchange of Thailand website and analyze by Ratio Analysis and Vertical Analysis. The results revile that: the company A showed better operation performance than the other two companies on higher liquidity, ability to make a revenue form assets investment, effective debt management to make the company stable, increased net profit. So, this company was interest to investment.